ARMED REVOLT IN MOSCOW IN DECEMBER, 1905 IN THE MIRROR OF ORIGINAL RUSSIAN PAREMIOLOGY ADAPTATION - Artur V. Zagrebelnyy (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2020)
The purpose of the article is to display some results of linguistic analysis of proverb adaptation motivated by the armed revolt in Moscow in December, 1905. The novelty of the research is that the adapted proverbs Moscow is not beautiful for its houses, but it is beautiful for its blood traces and Moscow brings no damage to Dubasov were chosen for the first time as objects of analysis in historical and cultural aspects by the method of historically distanced adapted proverb analysis, developed and approved by the author. The research method comprises elements of componential, contextual, logical and semiotic analysis along with the dictionary definition interpretations. The article states the following results: original proverbal sources for cultural transformation may be stated as identification potential of the adapted proverbs by establishing a prototypical comparison system based on structural model similarity and assigning both adapted and proverbal phrases in Russian to one of the four highest logical and semiotic invariant groups; the method of historically distanced adapted proverb analysis contributes to defining extralinguistic factors which caused formation of new language units; the judgments expressed by the adapted proverbs under studies were formulated; the types of adapted proverbs were singled out. The further studies of adapted paremiology motivated by social and political events in 1905–1907 Russia might be considered as research prospects with compliancy of adapted paremiology dictionary for the period of the first Russian revolution.